A New Technology for Precise Local Position Measurement - LPM - Stelzer, Andreas; Fischer, Alexander; Vossiek, Martin (International Microwave Symposium, 2004)
Precise measurement of the local position of moveable targets in three dimensions is still considered to be a challenge. With the presented local position measurement (LPM) technology a novel system, consisting of small and lightweight measurement transponders and a number of fixed base stations, is introduced. The new system is operating in the 5.8 GHz ISM-band and can handle up to 1000 measurements per second with accuracies down to few centimeters. Measurement results obtained with prototype boards demonstrate the feasibility of the proposed technology in practical applications. There exist a broad range of various applications, such as tracking of persons or controlling autonomous vehicles in industrial or logistic applications.
UnivIS-Import:2015-04-16:Pub.2004.tech.IE.LEH.anewte
Keywords: FMCW; GPS; LPM; Position measurement; Positioning